Comparação do uso de sistemas de aspiração aberto e fechado em récem-nascidos prematuros com peso abaixo de 1250 gramas - Luciana Puglia Pompeu (2014)
Endotracheal suctioning is required for the treatment of respiratory insufficiency of extremely low birth weight (ELBW) preterm newborns in mechanical ventilation, treated in Neonatal Intensive Care Units. However, this intervention is associated to several complications, such as atelectasis, hypoxemia, alterations in heart rate (HR) and arterial blood pressure, pneumothorax, variations in cerebral blood flow, which can lead to peri-intraventricular hemorrhage (PIVH). The closed suctioning system is being introduced in clinical practice and its use is suggested in newborn infants. However, there are no recommendations as to which system should be preferably used in preterm newborns. This study aimed at assessing and comparing the use of the open suctioning system (OSS) and the closed suctioning system (CSS) in preterm newborns with weight under 1250 grams in relation to the occurrence of oxygen desaturation and bradycardia before, during and after the suctioning procedure, during the first 72 hours of life. A randomized controlled trial was performed with a sample of 128 newborns, with gestational age 32 weeks, weight under 1250 g, using time-cycled and pressure-limited mechanical ventilation. HR and peripheral oxygen saturation (SpO2) data were collected before, during and after the suctioning procedure. The occurrence of barotrauma and PIVH was also investigated during the research. In the sample, 64 newborns (50%) were submitted to the OSS and 64 newborns (50%) were submitted to the CSS. The transfontanelar ultrasound was performed in the first 72 hours of life, aiming at verifying the occurrence of PIVH during the period the newborns was using mechanical ventilation. The occurrence of barotrauma was diagnosed by clinical and radiological assessment. The association between the type of system used and the clinical parameters of the newborns was performed by the Fisher Exact Test (for the occurrence of the parameters) and by the Mann-Whitney Test for the assessments of the number of occurrences in relation to the OSS and CSS groups. The results of the sample studied in the first 24, 48 and 72 hours of life, controlled by weight, showed higher oxygen desaturation in the group submitted to the OSS and in the 48-72-hour interval (p=0.036). No statistically significant difference was found for bradycardia during and after the procedure in the first 72 hours of life. Both groups were similar as for the occurrence of barotrauma and PIVH (p=0.305; p=0.999, respectively). In this study, the CSS offered advantages in relation to SpO2 stability during the suctioning procedure in preterms of ELBW between 48-72 hours of life and suggested lower demand of ventilatory support during the suction procedure, when compared to the OSS. The CSS can be thought as an alternative to prevent oxygen desaturation in preterm newborns of ELBW during the first days of life.